THE EFFECT OF THE PAIR CHECK TYPE COOPERATIVE MODEL ON MATHEMATICS LEARNING OUTCOMES OF 5TH GRADE STUDENT - Khuzaini, Nanang; Nasrulloh, Muhammad Farid (PROGRES PENDIDIKAN, 2023)
This research purpose to determine the effect of the pair check type of cooperative learning model on the mathematics learning outcomes of fourth grade. This quantitative research of pre-experimental research design that used in the form of a one group pretest posttest design. The population is all of the students in SDN Gunung Mulyo, Sedayu, Bantul. The sample in this study consisted in the entire class IV, with the generally 21 students. The date collection used a test and questionnaire method. The form of a written test has a form of multiple choice, while the questionnaire to have a form of a statement. The result of this study can be several conclusions, including: (1) the ability to understand the material before using the pair check type cooperative learning model in fourth grade students was generally categorized as moderate with the average score obtained by students is 62.6. (2) the ability to understand the material after using the pair check type cooperative learning model in fourth grade students was generally categorized as capable, this is evidenced by the average score obtained by students, which is 92.2. (3) the value of learning mathematics on the subject for fourth grade students showed that the significant value of 0,000. The significant value indicates 0,000 < 0,05 so H0 is rejected and H1 is accepted, which means that the significant value when used of the pair check type cooperative learning model on the fourth-grade students mathematics learning outcomes at SDN Gunung Mulyo, Sedayu, Bantul.